Cermin budaya: bagaimana seni mencerminkan dan mempertahankan identitas - sadiyah, halimatus (Maliki Interdisciplinary Journal, 2025)
This article delves into the pivotal role of art as a cultural language that reflects the history and identity of societies. Art serves not only as a medium for creative expression but also as a binder of traditions and a shaper of collective identity. The article highlights art’s ability to adapt to change, functioning as both a creative outlet and a tool of resistance. Art not only unifies communities but also serves as a window opening to cross-cultural insights. Within this framework, the article invites readers to explore how art acts as a crucial mirror, reflecting and enriching cultural identity, playing a vital role in preserving cultural heritage in the modern era. Art as a reflection of art history and a window Interculturalism acts as a window that opens a view into the history of society, allowing us to see the traces of the long journey of culture through creative mediums and art opens the door to intercultural insight, promotes understanding, respects diversity, and conveys relationships between various cultural groups.